The Single Degree of Freedom Simulation Model of Underwater Explosion Impact - Andrzej GRZĄDZIELA; Agata ZAŁĘSKA-FORNAL; Marcin KLUCZYK (Archives of Acoustics)
The hulls of naval ships are exposed to forces and moments coming from internal and external sources. Usually, these are interactions that can be described mathematically by harmonic and polyharmonic functions. The shock of UNDEX type (underwater explosion) works completely differently and its time waveform is difficult to describe with mathematical functions as pressure vs. time. The paper presents a simplification of physical and mathematical models of 1-D kickoff pressure whose aim is performance the simulation of the external force of the detonation wave. The proposed models were verified and tuned on naval, sea trials. The main goals of the proposed models are to perform simulation calculations of the detonation pressure for different explosion charge weights from different distances of the UNDEX epicentre for the design process of machine foundation. The effects of pressure are transformed as impulses exposed on shock absorber mounted at light shock machine.